Genetic aluminium resistance coupled with foliar magnesium application enhances wheat growth in acidic soil. (12th February 2021) - Kibria, Mohammad Golam; Barton, Louise; Rengel, Zed
Abstract: BACKGROUND: Soil acidity causes an increase in the solubility of toxic aluminium (Al), inhibiting root growth and limiting plant access to soil water and nutrients. Toxicity of Al decreases growth and development more in Al‐sensitive than Al‐resistant wheat ( Triticum aestivum L .) genotypes. Applying magnesium (Mg) may alleviate Al toxicity in acidic soil. It is unclear if growing Al‐resistant wheat, coupled with Mg application, will enhance wheat growth and physiological responses in acidic soil. Wheat was grown in the reconstituted acidic soil profile in a three‐factor glasshouse experiment comprising foliar Mg at [Mg] = 0 and 200 mg L −1 (using magnesium sulfate), wheat genotypes ES8 (Al sensitive) and ET8 (Al resistant), and four soil treatments [non‐amended soil (pH0.1 M CaCl2    4.0); 100% of the recommended lime dose in subsoil to raise pH to 6.0; or 20 mg Mg kg −1 soil to the whole soil profile (as magnesium sulfate or magnesium chloride)]. RESULTS: Applying foliar Mg to Al‐resistant wheat significantly increased shoot dry weight (24%), subsoil root dry weight (12%), subsoil coarse (>0.2 mm in diameter) root length (12%), net photosynthetic rate (28%), and total leaf area (10%) compared with plants not treated with foliar Mg. Combining foliar Mg application with subsoil liming increased the subsoil total root length by 1.3‐fold compared with zero foliar Mg. Without foliar Mg, subsoil liming and soil Mg amendment significantly (by 10%) enhanced shoot growth and total leaf area compared with non‐amended soil. CONCLUSION: Growing an Al‐resistant genotype coupled with applying Mg foliarly and to soil improved wheat growth in an acidic soil. © 2021 Society of Chemical Industry